KARIR EFEKTIF DALAM ORGANISASI SELULER - Nur Wening (Program Studi Manajemen, 2017)
The effectiveness in career management will certainly enhance a greater appropriateness between personnel and functions they are in charge of which ultimately results in developing their competence and placing the right persons in key positions. In traditional approach, promotion should be started from specific functions to higher ranks; in other words, an employee could only develop his career step by step. A recent development in career management to cope with the growth of the organization is the concept of a cellular organization consisting of independent groups or autonomous business units showing their independent existence and interacting one another to from a bigger organism. Career in such organization is known as protean career the aim or which is not just for promotion and improvement in salaries but also in psychological successes. This article tries to discuss how far van protean career be implemented in cellular organizations.